Lack of Association between Body Weight, Bone Mineral Density and Vitamin D Receptor Gene Polymorphism in Normal and Osteoporotic Women. Issue 4 (21st May 2013) - Poggi, Massimo; Aterini, Stefano; Nicastro, Laura; Chiarugi, Vincenzo; Ruggiero, Marco; Pacini, Stefania; Gulisano, Massimo
Abstract : In an ethnically homogeneous population of women living in Tuscany, Italy, the relationships between age, body weight, bone mineral density and the vitamin D receptor (VDR) gene polymorphism were studied, with the objective of recognizing patients at risk for osteoporosis. In 275 women bone mineral density was measured by Dual Energy X-rays Absorptiometry (DEXA). In 50 of them the individual genetic pattern for VDR was evaluated by DNA extraction followed by PCR amplification of the VDR gene, and digestion with the restriction enzyme BsmI. Age and bone mineral density were inversely related (R 2 = 0.298). Body weight was associated with bone mineral density (R 2 = 0.059), but not with age. In osteoporotic women, mean (± SD) body weight was 59.9 ± 6.5 Kg, lower than that recorded in non osteoporotic women (64.2 ± 9.4 Kg), even though not significantly different (p = 0.18). No association was found between VDR gene polymorphism, bone density or body weight. The performance of anthropometric and genetic components appear to be poor, and, at least for the time being, bone mineral density measurement by means of MOC-DEXA represents the optimal method to detect women at risk for postmenopausal osteoporosis.